Corrosion characteristic of multi-ring shield tunnel containing rubber concrete invert-filling under direct stray current - Shuo Yu; Hao Jin; Liangjie Gu; Peng Gui (Underground Space)
Stray current can cause corrosion of underground structural rebar, adding rubber particles to the invert-filling concrete is an effective prevent method to reduce stray current corrosion. In our research, the corrosion calculation model of multi-ring shield tunnel containing rubber concrete invert-filling was established, the coupling analysis of electric field and chemical field in composite structures was realized through mesoscale simulations, and the accuracy of calculation model was verified by full-scale test. Through calculation, the corrosion characteristic of segment rebar and bolt of multi-ring shield tunnel were investigated under different rubber content. The result shows that adding rubber particles to the invert-filling can not only reduce the corrosion current density of segment rebar and tunnel bolt effectively, but also affect the distribution form of rebar corrosion current density in both circumferential and longitudinal directions. When the rubber content increases from 5% to 20%, the maximum corrosion density of segment rebar and tunnel bolt will decrease from 31% to 58% and 30% to 32%, respectively. Under different stray current leakage modes, when the rubber content and input voltage are the same, the segment and bolt corrosion current density under single rail-two points leakage mode is greater than that in the two rails-single point leakage mode.